2000
DOI: 10.1016/s0002-9440(10)64809-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA and Protein Levels of β1 Integrin Variants in Human Prostate Carcinoma

Abstract: Alterations of integrin expression levels in cancer cells correlate with changes in invasiveness, tumor progression, and metastatic potential. The beta1C integrin, an alternatively spliced form of the human beta1 integrin, has been shown to inhibit prostate cell proliferation. Furthermore, beta1C protein levels were found to be abundant in normal prostate glandular epithelium and down-regulated in prostatic adenocarcinoma. To gain further insights into the molecular mechanisms underlying abnormal cancer cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…While there are data suggesting a role of β1 integrin in carcinogenesis, its precise functional role in PC is not well understood (21). Previous studies have indicated that β1 integrin and its splicing variants act by modulating cell adhesion, proliferation and survival (11,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are data suggesting a role of β1 integrin in carcinogenesis, its precise functional role in PC is not well understood (21). Previous studies have indicated that β1 integrin and its splicing variants act by modulating cell adhesion, proliferation and survival (11,22).…”
Section: Discussionmentioning
confidence: 99%
“…Variant β1C normally maintains adhesion and inhibits cell cycle progression, thereby inhibiting cell proliferation and migration (10,22,25). It is expressed by normal prostate tissues and is downregulated in PC; Perlino et al evaluated 33 PC and 5 normal prostate tissues and observed a down regulation of the mRNA and protein levels of β1C in 94% and 100% of cancer cases, respectively (21). In contrast, variant A was maintained in PC where its translation rates had increased more than twofold, which supports its role in cell proliferation and cancer cell invasion (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Two variants, b 1C and b 1A , have been shown to be expressed in prostatic epithelium. b 1C is shown to be expressed at both protein and mRNA levels in normal prostatic epithelial cells, but is markedly downregulated in adenocarcinoma (Fornaro et al 1996, 1998, Perlino et al 2000. b 1A has been found to be consistently upregulated in human prostate cancer (Knox et al 1994, Murant et al 1997, Goel et al 2007 as well as in a mouse model designated TRAMP (transgenic adenocarcinoma of mouse prostate) (Goel et al 2005).…”
Section: Integrin Deregulation In Prostate Cancermentioning
confidence: 99%
“…Changes in integrin levels have been reported to occur during tumorigenesis and metastasis of many tumors (Clezardin, 1998). In prostate cancer, the reported changes in integrins include increased expression levels of a3b1 and a6b1 (Schmelz et al, 2002), loss of b4 (Davis et al, 2001), and a decrease in a5b1c (Perlino et al, 2000) and a2b1 integrins (Dong et al, 1997). Integrins are implicated in regulating cellular processes such as adhesion, signaling, growth and differentiation, motility, survival, and gene expression (Miranti and Brugge, 2002).…”
Section: Introductionmentioning
confidence: 99%